Increasing Cytosine Base Editing Scope and Efficiency With Engineered Cas9-PmCDA1 Fusions and the Modified sgRNA in Rice - Wu, Ying; Xu, Wen; Wang, Feipeng; Zhao, Si; Feng, Feng; Song, Jinling; Zhang, Chengwei; Yang, Jinxiao (Frontiers in Genetics, 2019)
Base editors that do not require double-stranded DNA cleavage or homology-directed repair enable higher efficiency and cleaner substitution of targeted single nucleotides in genomic DNA than conventional approaches. However, their broad applications are limited within the editing window of several base pairs from the canonical NGG protospacer adjacent motif (PAM) sequence. In this study, we fused the D10A nickase of several Streptococcus pyogenes Cas9 (SpCas9) variants with Petromyzon marinus cytidine deaminase 1 (PmCDA1) and uracil DNA glycosylase inhibitor (UGI) and developed two new effective PmCDA1-based cytosine base editors (pBEs), SpCas9 nickase (SpCas9n)-pBE and VQR nickase (VQRn)-pBE, which expanded the scope of genome targeting for cytosine-to-thymine (C-to-T) substitutions in rice. Four of six and 12 of 18 target sites selected randomly in SpCas9n-pBE and VQRn-pBE respectively were base edited with frequencies of 4%–90% in T0 plants. The effective deaminase window typically spanned positions 1 to 7 within the protospacer and the single target C showed the maximum C-to-T frequency at or near position 3, counting the end distal to PAM as position 1. In addition, the modified single guide RNA (sgRNA) improved the base editing efficiencies of VQRn-pBE with 1.3- to 7.6-fold increases compared with the native sgRNA, and targets that could not be mutated using the native sgRNA were edited successfully using the modified sgRNA. These newly developed base editors can be used to realize C-to-T substitutions and may become powerful tools for both basic scientific research and crop breeding in rice.